Management of choledocholithiasis in an emergency cohort undergoing laparoscopic cholecystectomy: a single‐centre experience. Issue 7 (7th November 2013) - Poh, Benjamin; Cashin, Paul; Bowers, Kaye; Ackermann, Travis; Tay, Yeng Kwang; Dhir, Arun; Croagh, Daniel
Abstract Introduction Minimally‐invasive options for the management of choledocholithiasis in patients undergoing laparoscopic cholecystectomy include laparoscopic and endoscopic approaches. This study reviews the effectiveness of both approaches in an emergency setting. Methods A retrospective chart review was performed for a cohort of patients who underwent laparoscopic cholecystectomy. Outcomes assessed were duct clearance, the number of procedures performed (NPP), length of stay (LOS) and complication rate. Results A total of 182 patients who underwent emergency laparoscopic cholecystectomies received intervention for choledocholithiasis. The duct clearance rate was lower in the laparoscopic group, 63% versus 86% (P = 0.001). However, the median NPP was also lesser in the laparoscopic group, 1 (interquartile range (IQR) 1–2) versus 2 (IQR 2–2) (P < 0.001), as was the median LOS, 5 days (IQR 3–8) versus 7 days (IQR 6–10) (P = 0.009). Forty‐eight laparoscopic endobiliary stents were attempted; stent deployment was successful in 37 patients. A larger proportion of patients with laparoscopic endobiliary stents had duct clearance by endoscopic retrograde cholangiopancreatography (ERCP) compared with those without, although this was not statistically significant (P = 0.208). Conclusion Laparoscopic clearance is not as effective as post‐operative ERCP in an emergency cohort, but is associated with fewer procedures required and a shorter inpatient stay. Thus, laparoscopic clearance may still be an attractive option for surgeons especially where conditions are favourable during an emergency laparoscopic cholecystectomy.